Wasita Rini: Pemikiran Ki Hajar Dewantara Dalam Pendidikan Perempuan (Sutasoma : Jurnal Sastra Jawa, 2022)
The discussion on Women's Education is never finished. Women as domestic workers or tied up in public spaces are not asked to be debated; they are used as a discourse for discussion everywhere. This study aims to brainstorm in the discussion of how education is applied to women. The research method used is the historical method. The results of the research, which focused on (1) Women's Issues in the Wasita Rini Period, (2) Wasita Rini as the Fruit of Thoughts on Education for Women, (3) Wasita Rini and Education for Women Pre and PostIndependence, showed that Ki Hajar Dewantara as It turns out that the founders of Indonesian education have initiated education for women through their works, one of which is Wasita Rini's fiber. Ki Hajar Dewantara responded wisely to the strong waves that world female leaders exhaled at that time; he involved women's rights in all fields, one of which was related to gender injustice, but by still precipitating eastern norms. Therefore, women leaders in Indonesia can use this research as a reflection; women today are responsible for continuing the struggle. Keywords: Wasita Rini, Ki Hajar Dewantara, Pendidikan Perempuan